Pertanggungjawaban Pidana dan Perlindungan Hukum terhadap Anak dalam Tindak Pidana Narkotika - Leni Dwi Nurmala; Yoslan K. Koni; Dince Aisa Kodai (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2022)
Â Â The circulation of narcotics in Indonesia has spread to various circles, not even a few children are victims of the narcotics circulation. The involvement of children as narcotics users and the involvement of children as perpetrators of narcotics trafficking, so that eradication and prevention must be carried out specifically and requires the involvement of various parties. In this study will discuss how the legal protection of children in narcotics crimes. The method used in this writing is normative juridical writing with a statutory approach and literature study. The results of the discussion obtained by children who are caught in the law or children in conflict with the law (ABH), especially the legal protection of children in narcotics crimes must be able to realize restorative justice with settlement efforts that prioritize the best interests of the child, with the aim of finding a fair legal settlement. as well as prioritizing the recovery of children's conditions and providing protection for the rights of children who are in conflict with the law so as to avoid handling that violates legal procedures during the criminal justice process. This is carried out based on the mandate of Law no. 11 of 2012 concerning the Juvenile Criminal Justice System and Law no. 35 of 2014 concerning Child Protection.